American Income Inequality in a Cross-National Perspective: Why Are We So Different? - Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1997)
Increasingly the rich nations of the world face a common set of social and economic issues: the cost of population aging, a growing number of single parent families, the growing majority of two-earner families, increasing numbers of immigrants from poorer nations, and in particular, rising economic inequality generated by skill-based technological change, international trade and other factors. All of these nations have also designed systems of social protection to shield their citizens against the risk of a decline in economic status due to unemployment, divorce, disability, retirement, and death of a spouse. The interaction of these economic and demographic forces and social programs generates the distribution of disposable income in each of these nations. The experiences and consequences of nations in dealing with issues of economic and social inequality is the subject of this paper.
Keywords: 330; Einkommensverteilung; USA; Welt